Influence of Long-Term Space Flight on Mechanical Properties of the Human Triceps Surae Muscle: Electro Mechanical Delay and Musculo-Tendinous Stiffness - A. Koryak Yuri (Journal of Skeletal Muscle, 2017)
The effects of long-term space flight on human triceps surae (TS) muscle function and electromechanical delay (EMD) have been investigated. Voluntary and electrically evoked contractions of the TS were obtained from 7 male cosmonauts 30 days before and 3 days after landing. For all cosmonauts the isometric maximal voluntary contraction was reduced by 41.7 % (p < 0.01), whereas the electrically evoked maximal tetanic contraction force (Po) was found to decrease by 25.6 % (p < 0.05). Force deficit increased by 50 % (p < 0.001). This suggests that most of the force loss is due to a reduction in motor drive (motor control). The decrease in Po was associated with a significant increase of the corresponding maximal rates of tension development (43.7 %). The twitch tension (Pt) was not significantly changed and the Pt/Po ratio was increased by 46.7 % (p < 0.05) after space mission. The twitch time-to-peak tension of the TS increased by 7.7 %, but half-relaxation time decreased by 20.6 %. Force-velocity properties of the TS calculated according to a relative scale of voluntary contraction development significantly decreased. The calculations of the same properties of electrically evoked contraction development did not differ substantially from the initial physiological state. Total reaction time (TRT), pre-motor time (PMR) and motor time or EMD were determined. In response to a supramaximal single electrical pulses applied to the tibial nerve, the latent period between the M-wave and Рt beginning was determined. The voluntary contraction EMD increased by 34.1 %; but PMR and TRT decreased by 19.0 and 14.1 %, respectively. The EMD of electrically evoked contraction did not significantly change. Thus, the comparison of the mechanical alterations recorded during voluntary contractions and in contractions evoked by electrical stimulation of the motor nerve, suggests that weightlessness not only modifies the peripheral processes associated with contractions, but also changes central and/or neural command of the contraction.
Keywords: space flight